IPAD IN LANGUAGE PEDAGOGY: TEACHERS ATTITUDE - Gusnita Ariani; Magdad Hatim; Masagus Firdaus (Universitas PGRI Palembang, 2024)
Despite the benefits technology brings to English learning at school, few teachers were still taking advantage of it. Not only was the iPad was a learning medium with short and medium-term used, it also serves as a device that helps improved student education. The objective of the research is to identify the types of the English teachers attitude towards iPad in teaching and learning processes. However, a descriptive qualitative study was conducted to investigate the attitude of English teachers towards iPad in teaching and learning process at IT Harapan Mulya Junior in Palembang. Questionnaires and interviews were used to collect data. Data analysis was processed in the form of reduction data, display data, and conclusion drawing and verification data. The results showed that the English teachers provided 90 utterances consisting of 31 cognitive attitudes, 26 conative attitudes, 24 affective attitudes, and 9 evaluative attitudes. Cognitive attitudes was most often exhibited by the teachers. While the lowest was the evaluative attitude.